Life orientation and chosen sociomedical indicators of women suffering from type 2 diabetes - Olszak, Cecylia; Nowicka, Elżbieta; Baczewska, Bożena; Kropornicka, Beata; Łuczyk, Robert Jan; Krzyżanowska, Ewa; Mróz, Anna; Zwolak, Agnieszka; Daniluk, Jadwiga (Journal of Education, Health and Sport, 2018)
The aim of the study: In the process of dealing with diabetes every day the sense of coherence plays an important role. This construct in the salutogenesis theory determines the ability ofan individual to skilfully utilize the available resources for their own wellbeing. In many works the influence of demographic, social and clinical factors on the sense of coherence of people suffering from diabetes was analysed. However, little attention was paid to the detailed description of this issue among women suffering from diabetes. The aim of the study was to determine the relationship between the sense of coherence and the chosen sociomedical variables among women suffering from type 2 diabetes. Material and methods: In total 131 women suffering from type 2 diabetes treated at the Endocrinology Hospital and the Diabetes Outpatient Clinic were the subject of this research. The women who were selected for this research were 40 years old, had suffered from diabetes for over one year and gave permission to take part in the study.The study was conducted based on the original questionnaire comprising the data concerning: age, educational background, place of residence, marital status and professional activity. The questionnaire allowed gathering medical data like: duration of the disease, BMI index, HbA1c value or the method of diabetes treatment.Life Orientation Questionnaire (SOC-29) by A. Antonovski [4] in a Polish language version was used to determine the rating of the sense of coherence. Results. The level of the sense of coherence of the surveyed women suffering from diabetes was between 47 and 197 points. Statistically significant differences were not observed (p > 0.05) in the ratings of the sense of coherence versus the place of residence, education or marital status. There were no significant relationships (p > 0.05) between the sense of coherence, its components and the method of treatment, HbA1c value and the disease duration time. A statistically relevant difference (p < 0.05) between the sense of coherence, its components and the age of respondents was demonstrated. Moreover, a statistically relevant difference was proven (p < 0.05) between the sense of coherence and Body Mass Index. Furthermore, a statistically significant difference (p < 0.05) between the sense of coherence, its components and the professional activity of the research subjects was found. Conclusions: 1.The level of sense of coherence was lower than the standard average norms as applied by A. Antonovsky (133-160 points) among women suffering from type 2 diabetes. 2. Women who were professionally active and mature stood out with a high level of the sense of coherence and its components. 3. Women suffering from type 2 diabetes with normal body weight had high a level of the sense of coherence.